THE CRISIS OF THE ARCHAICAL THINKING OF THE PRINCIPAL METAPHYSICAL PROBLEM OF THE ANCIENT GREEK PHILOSOPHY - Vytautas Rimvydas Rimvydas Litvinas (Problemos)
An attempt is made to evaluate the teachings of the ancient philosophers Parmenides and Heraclitus. These teachings are interpreted as an outcome of the destruction of symbolic thinking. On the basis of the material gathered and elaborated by Lucien Levy-Bruhl, Mircea Eliade and Carl G. Jung the systems of Parmenides and Heraclitus are treated as a consequence of the split of the symbol of the "psuchic reality" in the process of differentiation of psychic functions. The twofold character of the archaically perceived reality engenders the radical question of the Ancient Greek philosophy: what is reality, i. e., "that, which is"? Although the philosophy of Heraclitus and of Parmenides provide essentially opposite answers to that question, nevertheless, the problem itself is in both cases inspired by the contradictory nature of the "psychic reality" of the cognizant agent. The author attempts to show that both outlooks are merely two different modes of the same "prelogical thinking". In that sense, both the "rational", and the "irrational" thinking should be seen as emeriging from the same sourse, albeit with different value systems: Heraclitus gave priority to the dynamics of the symbol, whereas Parmenides underlined the value of the "stability" and "identity" of the symbol. In fact, both of these "modes of being" are related by the "magic" quality of the archaic thinking - by the articipation mystique. The different answers given to that sort of guestion imply different ensuing difficulties: the followers of Heraclitus encounter the problem of the identity of the name, whereas Parmenides has to face the problem of lie, or, in other words, the problem of how to think non-being.